Answer:
5/9x+y=2/3
Step-by-step explanation:
-Thank you-
y= 2x + 3
y= -3x + 3
Answer:
(0, 3 )
Step-by-step explanation:
Given the 2 equations
y = 2x + 3 → (1)
y = - 3x + 3 → (2)
Since both equations express y in terms of x we can equate them, that is
2x + 3 = - 3x + 3 ( add 3x to both sides )
5x + 3 = 3 ( subtract 3 from both sides )
5x = 0 ⇒ x = 0
Substitute x = 0 into (1)
y = 0 + 3 = 3
Solution is (0, 3 )
Answer:
108 pounds of mulch.
64 pounds of gravel.
Step-by-step explanation:
Let x be the amount of mulch sold and y be the amount of gravel sold.
We have been given that a supplier sells 2 1/4 pounds of mulch for every 1 1/3 pounds of gravel.
We can represent this information as:
We are also told that the supplier sells 172 pounds of mulch and gravel combined. We can represent this information as:
From equation (1) we will get,
Substituting this value in equation (2) we will get,
Now let us have a common denominator.
Therefore, the supplier sold 64 pounds of gravel.
Upon substituting y=64 in equation (2) we will get,
Therefore, the supplier sold 108 pounds of mulch.
Hey there!
We can solve inequalities just like equations. There is only one difference though. If you ever multiply or divide both sides by a negative number, you "flip" the inequality sign.
First, let's undo the parentheses.
2x-24+24<4x+20
We simplify.
2x<4x+20
We subtract 4x from both sides.
-2x<20
We divide both sides by -2 (we will need to flip the inequality sign).
x>-10
I hope this helps!